Application of Green Innovation and Corporate Social Responsibility to Increase Company Value in Every Firm Life Cycle : Systematic Literature Review - Eni Puji Estuti; Natoil Natoil (Asian Journal of Management, Entrepreneurship and Social Science, 2023)
The attention of management and practitioners is currently directed towards green innovation. Environmental damage that occurs in various countries has made stakeholders, including governments as policy makers, companies and society, pay serious attention. Increasing global concern for the environment has encouraged companies to implement increased pro-environmental practices and activities, so they tend to become more competitive and environmentally friendly. The purpose of this article is to provide green innovation (GI), CSR, company value and company life cycle methods from a comprehensive review, analyzing the article based on a systematic literature review. This study analyzed articles published from the first article, namely 1952, discussing the topic of corporate values and firm life cycles until 2023. This study analyzed articles published from the first article, namely 1952, discussing the topic of corporate values and firm life cycles until 2023. There are 5 top topics explored in this study, namely: corporate social responsibility, environmental innovation, life cycle, value and company growth. But, the discussion raised around the above topics is mostly CSR practices, sustainability, environmental performance in each company's life cycle. Article collection using Publish or Perish with Google Scholar (1,002) and Proquest (71) data base so that the total data is 1,073. Furthermore, the data is processed using Vos Viewers to produce more real mapping.